2006
DOI: 10.1042/bc20050020
|View full text |Cite
|
Sign up to set email alerts
|

PKB/AKT is involved in resumption of meiosis in mouse oocytes

Abstract: Background information. In fully grown mouse oocytes, a decrease in cAMP concentration precedes and is linked to CDK1 (cyclin-dependent kinase 1) activation. The molecular mechanism for this coupling, however, is not defined. PKB (protein kinase B, also called AKT) is implicated in CDK1 activation in lower species. During resumption of meiosis in starfish oocytes, MYT1, a negative regulator of CDK1, is phosphorylated by PKB in an inhibitory manner. It can imply that PKB is also involved in CDK1 activation in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
101
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 48 publications
13
101
0
Order By: Relevance
“…TOR-dependent phosphorylation of Akt in starfish oocytes Akt activation has previously been reported in mouse and bovine oocytes (Tomek and Smiljakovic, 2005;Kalous et al, 2006); however our present observations represent the first indication that the TOR protein is required for the phosphorylation of both the TM and HM in oocytes. Although other components of the sfTOR complex remain to be identified, TORC2 rather than TORC1 is likely responsible for phosphorylation of both sites in starfish oocytes (Figure 2c, Supplementary Figures S3c-e).…”
Section: Mutual Phosphorylation Of Akt On Conserved Motifs D Hiraoka supporting
confidence: 64%
“…TOR-dependent phosphorylation of Akt in starfish oocytes Akt activation has previously been reported in mouse and bovine oocytes (Tomek and Smiljakovic, 2005;Kalous et al, 2006); however our present observations represent the first indication that the TOR protein is required for the phosphorylation of both the TM and HM in oocytes. Although other components of the sfTOR complex remain to be identified, TORC2 rather than TORC1 is likely responsible for phosphorylation of both sites in starfish oocytes (Figure 2c, Supplementary Figures S3c-e).…”
Section: Mutual Phosphorylation Of Akt On Conserved Motifs D Hiraoka supporting
confidence: 64%
“…4H) in Cox-2 Ϫ/Ϫ females, we further asked whether these processes under the influence of PGE 2 utilize differential signaling cas- cades during oocyte maturation. Early studies have demonstrated that cumulus expansion in response to gonadotropin or other stimuli depends on multiple signaling pathways, including cAMP/PKA (42-45), ERK1/2 (34, 46 -49), p38 MAPK (34,49), as well as PI3K-Akt signaling (40,41). Thus, we next used selective antagonists of these pathways and tested their effects under PGE 2 stimulation in cumulus cells.…”
Section: Pge 2 Directs Cumulus Cell Expansion and Survival During Oocmentioning
confidence: 99%
“…Increasing evidence points toward the involvement of the PI3K-Akt signaling cascade in gonadotropin-induced oocyte meiotic maturation (40,41). Thus, we first examined the expression of phospho-Akt in COCs in wild-type and Cox-2 Ϫ/Ϫ mice during in vivo oocyte maturation.…”
Section: Pge 2 Directs Cumulus Cell Expansion and Survival During Oocmentioning
confidence: 99%
“…At GVBD, phosphorylated PKB has been observed on the centrosome. This result shows that one function of PKB is to initiate the activation of CDK1 [29]. Furthermore, while the mechanism of PKB activation in mouse oocytes is not understood, it may be linked to the ability of high levels of cAMP to inhibit PKB activity [4].…”
Section: Gvbd or Resumption Of The First Meiosismentioning
confidence: 95%
“…PKB is likely involved in the maturation of oocytes, probably independent of MPF activation. A peak in PKB activity has been observed at approximately the time of GVBD and activity of PKB declined at MI in pig oocytes [29]. Kalous et al [29] found that PKB is related to CDK1 activation and participates in resumption of meiosis in mouse oocytes.…”
Section: Gvbd or Resumption Of The First Meiosismentioning
confidence: 99%